Aktivitas Antioksidan Ekstrak Etanol Kayu Manis (Cinnamomum burmani) Secara In Vitro / Antioxidant Activities Of Cinnamon (Cinnamomum burmani) In Vitro - Antasionasti, Irma; I, Jayanto (Jurnal Farmasi Udayana, 2021)
ABSTRACT Cinnamon (Cinnamomum burmani) is a spice that can be used as an additive in food and cakes as well as a pharmaceutical ingredient in the pharmaceutical industry. Therefore, the exploration of cinnamon as a natural antioxidant is highly needed. The study aims is to investigate the antioxidant activity of cinnamon using the DPPH, ABTS radical assay and ferric reducing activity power (FRAP) as well as total phenolic and total flavonoids. Cinnamon was extracted using the maceration technique by ethanol 96% as a solvent and tested for antioxidant activity. The antioxidant activity of DPPH, ABTS, and FRAP that showed by the ethanol extract of cinnamon were 1.939 ± 0.055 ?g/mL; 2,235 ± 0.014 ?g/mL; and 1415.705 ± 38.609 mg of ascorbic acid/gram extract, respectively. The antiradical activity of the ethanol extract of cinnamon was lower than vitamin C, namely 0.554 ± 0.003 ?g/mL (DPPH) and 0.813 ± 0.028 ?g/mL (ABTS). The antioxidant activity provided by the ethanol extract of cinnamon was influenced by the total phenolic content and total flavonoids, respectively 75.685 ± 1.408 % EAG and 60,546 ± 0,670% EK. Cinnamon has very strong antioxidant activity, contains high amounts of total phenolic and total flavonoids so that it has the potential to be a food additive (antioxidant) in the food and pharmaceutical industries.